Design Development and In Vitro Evaluation of Novel Orally Disintegrating Tablets in Fixed-dose Combination Containing Ambroxol Hydrochloride and Cetirizine Hydrochloride Prepared by Direct Compression Technique - Sharma, Deepak (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the study deals with the design development and in vitro evaluation of orally disintegrating tablets (ODTs) of ambroxol hydrochloride (AMB HCl) and cetirizine hydrochloride (CTZ HCl) in combination for the treatment of respiratory disorders by using superdisintegrants in combination with suitable binder and excipients. Direct compression method was used to prepare tablets. Materials and Methods: In the present research work, the different concentrations of sodium starch glycolate (SSG) as superdisintegrant were used to optimize the concentration of SSG in the formulation of ODTs. Different concentrations of microcrystalline cellulose (MCC) and polyvinylpyrrolidone K-30 were also studied along with optimized SSG concentration. The tablets were evaluated for hardness, friability, weight variation, wetting time, in vitro disintegration time (DT), and % age drug content uniformity. Optimized formulation was further evaluated by in vitro release study, drug-excipient compatibility, and accelerated stability study. Result and Discussion: The optimized concentration of SSG was found to be 4% on the basis of least DT. MCC in 1% was selected as optimum binder concentration on the basis of least DT. ODTs passed all the quality control tests, namely, weight variation, hardness, friability, in vitro DT, % age drug content uniformity, and wetting time. The formulation satisfied the requirements of FDA for rapid dissolving tablets and allowed more than 85% drug to be released within 30 min. The Fourier-transform infrared study reveals that there was no interaction between drug and excipients. The accelerated stability study shows that formulation is quite stable at normal temperature and humidity conditions as well as at extreme temperature conditions. Conclusion: It was concluded that by adopting a systematic formulation approach, ODT of AMB HCl and CTZ HCl in fixed-dose combination could be formulated using superdisintegrants in combination with appropriate binder and excipients which was found to be economical and industrially feasible.